Loquat (Eriobotrya L.) - Badenes, María L.; Lin, S. Q.; Liu, C.; Huang, X. (Springer, 2017)
Loquat (Eriobotrya japonica Lindl., Rosaceae, Maloideae) is a subtropical evergreen fruit tree that blooms in fall and early winter. Records on loquat in China spanover 2,000 years. Loquat species are native to the South East of China (Fig. 1). The medium and low region of Dahube river and South East of the Gongga Montains are considered the primary center of origin for Eriobotrya japonica (Zhang et al., 1990), with the Yunnan region as a secondary center (Yang et al., 2005). The loquat cultivated in Japan was introduced from China in ancient times and its cultivation in Japan was described as early as 1180 (Ichinose, 1995). In 1784, the loquat was introduced from Guangdong into the National Garden at Paris, and in 1787 it was introduced into the Royal Botanical Gardens at Kew, England. Thereafter, loquat was distributed around the Mediterranean countries, including Algeria, Cyprus, Egypt, Greece, Israel, Italy, Spain, Tunisia and Turkey. Sometime between 1867 and 1870, loquat was introduced to Florida from Europe, and to California from Japan. Chinese immigrants are assumed to have carried the loquat to Hawaii (Morton, 1987). Cultivation spread to India and Southeastern Asia, the East Indies, Australia, New Zealand, Madagascar, and South Africa. Loquats are now distributed in many Asian countries, for example, Laos, Nepal, Pakistan, South Korea, and Vietnam; in Armenia, Azerbaiian and Georgia; and in the Americas, including Argentina, Brazil, Chile, the mountains of Ecuador, Guatemala, Mexico, and Venezuela. Generally, loquats are found between latitudes 20 and 35. North or South. but can be cultivated up to latitude 45. under marine climates (Lin et al., 1999). Currently, the crop is grown in temperate and subtropical areas, sharing the same environmental areas as citrus.